DIAMOND SMOOTHING EFFORTS AND THEIR CONTROL - Dubrovets Lyudmila Vladimirovna; Yuldoshev Mirzobek Nurilloevich (Galaxy International Interdisciplinary Research Journal, 2021)
The article covers analysis of various methods of cutting forces measurement at diamond smoothing and their description, advantages and disadvantages.